STUDI SIMULASI PENGARUH VARIASI UKURAN PIEZOELEKTRIK DAN KEBISINGAN LOKOMOTIF KERETA TERHADAP TEGANGAN DENGAN MENGGUNAKAN ANSYS - Utomo, Ilham Satrio; Prasetya, Henry Widya; Kurniawan, Moch Aziz (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2020)
The purpose of this study was to determine the effect of variations in electrical piezo size and train locomotive noise to the voltage generated using ANSYS. Pezoelectric Size variations used are 1x1, 3x3, 5x5 (cm). As for the noise variations used are 93, 96, 98, 100 (dB). The method used is the numerical method; in this case Finite Element Analysis (FEA) with the help of ANSYS Static structural program. The results showed that using piezoelectric 5x5 cm and at 100 dB noise produced a maximum voltage of 158.12 mV.